2017
DOI: 10.1002/2016gl071980
|View full text |Cite
|
Sign up to set email alerts
|

Geographical differences in the tropical precipitation‐moisture relationship and rain intensity onset

Abstract: In this study, we show that the well‐documented exponential increase in the precipitation‐water vapor (P‐r) curve over tropical oceans also applies to tropical land but that the land curve starts its exponential increase at smaller values of column moisture than over ocean. We demonstrate that daytime surface heating contributes to this characteristic shape of the land P‐r curves. There is also significant geographical variation in the shape of the P‐r curve within land and ocean regions, with the Amazon, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…To calculate the occurrence frequency, first the number of occurrences in each precipitation rate bin is divided by the total number of days for each forecast lead time and grid point. Then the average across the first 4 weeks over the Indo‐Pacific Ocean (60–180°E, 15°S to 15°N) is computed from this; land area is masked out since convection is typically forced by the diurnal cycle more than moisture‐convection coupling (Ahmed & Schumacher, ). Only control simulations are used from the reforecasts in these calculations.…”
Section: Mjo Processes and Mean Statementioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the occurrence frequency, first the number of occurrences in each precipitation rate bin is divided by the total number of days for each forecast lead time and grid point. Then the average across the first 4 weeks over the Indo‐Pacific Ocean (60–180°E, 15°S to 15°N) is computed from this; land area is masked out since convection is typically forced by the diurnal cycle more than moisture‐convection coupling (Ahmed & Schumacher, ). Only control simulations are used from the reforecasts in these calculations.…”
Section: Mjo Processes and Mean Statementioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres from this; land area is masked out since convection is typically forced by the diurnal cycle more than moisture-convection coupling (Ahmed & Schumacher, 2017). Only control simulations are used from the reforecasts in these calculations.…”
Section: 1029/2019jd031139mentioning
confidence: 99%
“…This exponential behavior in the moisture-precipitation relationship has repeatedly been found in the studies that used various types of observations of water vapor and precipitation (Gilmore, 2015;Holloway & Neelin, 2009;Neelin et al, 2008;Raymond et al, 2007Raymond et al, , 2011. It is worthwhile to note that recent studies have found that the moisture-convection coupling is the strongest over tropical oceans, and it becomes weaker in coastal areas (Bergemann & Jakob, 2016) and over land (Ahmed & Schumacher, 2017) where the convection is typically forced by sea breeze or daytime surface heating. the coefficients a d and P r obtained by Bretherton et al (2004) (e.g., Adames & Kim, 2016Liu & Wang, 2016;Sobel & Maloney, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both observational (33)(34)(35)(36) and modeling (37) studies have suggested that the transition to deep convection is highly sensitive to the availability of moisture in the lower free troposphere, thus explaining the observed precipitation-column-water-vapor relation (33,36,(38)(39)(40)(41)(42)(43). Previous efforts have indicated that the observed sharp increase in precipitation as a function of column water vapor is associated with effects of air entrained in the lower troposphere (33,36).…”
mentioning
confidence: 99%